Investigating Eating Behaviors and Symptoms of Oral Frailty Using Questionnaires - Tsukasa Hihara; Takaharu Goto; Tetsuo Ichikawa (MDPI AG, 2019)
A questionnaire survey was conducted to investigate eating behavior and the subjective symptoms of oral frailty, and to examine the relationship between them. A total of 744 subjects with ages over 65 years were included. The questionnaire comprised 18 question items indicating eating behavior and seven question items indicating oral frailty. All items were assessed according to 4 grades on a scale of 1 (not applicable) to 4 (applicable). The total score of oral frailty gradually increased with age. Regarding the scores for “eating recognition” and “eating habits”, no changes were observed, however the scores for “eating action” demonstrated a decreasing tendency with age and the scores of ≥ 85 years age group was significantly lower than the 65−69, 70−74, and 75−79 years age groups. As a result of multiple regression analysis, among the significant independent variable, the scores of “I do not chew foods well” under the category of “eating action” showed the highest standard partial regression coefficients for dependent variable of symptoms of oral frailty. The significant association was found between the eating behavior and subjective symptoms of oral frailty, and this study suggests that the good chewing habit might be an important criterion for the prevention of oral frailty.